Sudden cardiac death after alcohol intake: classification and autopsy findings - Lauri Holmström; Janna Kauppila; Juha Vähätalo; Lasse Pakanen; Juha Perkiömäki; Heikki Huikuri; Juhani Junttila (Scientific Reports, 2022)
Abstract Alcohol is known to have an immediate effect on cardiac rhythm, and previous studies have found that a notable proportion of sudden cardiac deaths (SCD) occur after alcohol intake. The objective of the present study was to investigate the association between the timing of alcohol intake and SCD. Our study population is drawn from the Fingesture study, which includes 5869 consecutive SCD cases from Northern Finland who underwent medicolegal autopsy 1998–2017. Toxicological analysis was performed if there was any suspicion of toxic exposure, or if there was no obvious immediate cause of SCD at autopsy. We found that 1563 (27%) of all SCD victims had alcohol in blood or urine at autopsy (mean age (61 ± 10 years, 88% male). Eighty-six percent of alcohol-related SCD victims had higher urine alcohol concentration than blood alcohol concentration, referring to the late-stage inebriation. These results suggest that the majority of alcohol-related SCDs occur at the late stage of inebriation.